The early impact of the revised Leaving Certificate grading scheme on student perceptions and behaviour - Selina MacCoy; Delma Byrne; Jessica O'Sullivan; Emer Smyth (The Economic and Social Research Institute (ESRI), 2019)
This study shows an increase in the number of students taking higher level subjects for the Leaving Certificate. However, the increase was less pronounced in DEIS schools and smaller schools.
Keywords: 330